A Paradigm Shift in Government Initiatives on Dairy and Pork Quality and Safety in Informal Markets in Assam, India - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Results from a promising food safety intervention designed and tested by CGIAR combined with long-term engagement with the Government of Assam have led to changes in the government's posture towards the informal dairy and pork sectors. The World Bank and the Government of Assam in India are scaling a food safety intervention designed and tested by ILRI in informal dairy value chains in 16 districts and in informal pork value chains in 13 districts, expected to benefit millions of consumers.